AJAR UP 2021 as a basic introduction to sign language learning - Theresia Yohana; Hanifa Athaya Rafida; Vincent Natanael Hasibuan; Nova Ulhasanah; I Wayan Koko Suryawan (Universitas Muhammadiyah Magelang, 2022)
AJAR UP is one of the activities of the Environmental Engineering study program students at Universitas Pertamina, realizing good learning for the community. During this period, AJAR UP focused on sign language learning activities. AJAR UP activities aim to expand soft skills obtained in the academic field and in the non-academic field in the form of language, which can later be implemented in the workplace for the general public and also for Universitas Pertamina students. This activity was attended by 28 people on Saturday, December 18, 2021. AJAR UP activities so far, which have been open for free, have opened new learning opportunities for the general public and Universitas Pertamina students to learn sign language. Based on the feedback provided, it can be concluded that the participants stated that sign language is essential to learn, especially in today's era. Therefore, AJAR UP activities indirectly open up learning opportunities for the community and Universitas Pertamina students about culture and some of the methods used in sign language.